Perbaikan Ergonomi untuk Menurunkan Risiko akibat Pekerjaan yang Berulang di Grease Plant Workstation - Dian Mardi Safitri; Aston Benedict Wartono (UIN Sultan Syarif Kasim Riau, 2016)
Manual and repetitive activity in a grease filling production brings an ergonomics risk to theoperator. OCRA Index, Strain Index, Quick Exposure Checklist and Nordic Body Map were used in thepreliminary study to identify and measure the risk. There were medium and high risk and the improvementwas needed immediately due to the repetitiveness work. The aim of this study is to identify the risk due tothe repetitiveness and to improve the workstation to minimize the risk. Analytical Hierarchy Process wasused to decide what kind of improvement would be taken. Workstation redesign and product redesign wasselected to be implemented. Improvement on conveyor and grease drum was proposed to minimize therepetitiveness risk. The result of the study show that the repetitiveness risks were categorized asacceptable based on the OCRA Index score.Keywords: ergonomics risk, redesign, repetitiveness, workstation